Workplace Violence against Residents in Emergency Department and Reasons for not Reporting Them; a Cross Sectional Study - Hedayati Emam, Gilava; Alimohammadi, Hossein; Zolfaghari Sadrabad, Akram; Hatamabadi, Hamidreza (Archives of Academic Emergency Medicine, 2018)
Introduction: Due to the stressful nature of emergency Department (ED), residents in ED are at risk of violence from patients or their associates. This study aimed to determine the prevalence of workplace violence against ED residents and the reasons for not reporting them. Methods: This cross-sectional study was conducted on ED residents of three educational hospitals, Tehran, Iran, during 2015. The national questionnaire about workplace violence was used for data gathering. In addition, prevalence of reporting the violence and the reasons for not reporting them were determined. Results: 280 questionnaires were analyzed. The mean age of residents was 32.2 ± 4.6 years (58.4% female). 224 (80%) residents stated that they had not passed any educational courses on violence management. The most prevalent type of violence was verbal (90.7%) and patients’ associates (85.4%) were the most common source of aggression. The frequency of physical violence was higher in male aggressors (p = 0.001), resident age > 30 years (p = 0.044), aggressor age > 30 years (p = 0.001), and night shift (p = 0.001). The same trend was observed regarding verbal and racial-ethnic violence. There was no significant relationship between residents’ sex, resident's specialty, and presence of security and police with frequency of violence. 214 (76.4%) residents did not report the violence, and the main reasons for not reporting from their viewpoint were uselessness of reporting (37.4%) and insignificance of the violence (36.9%). Conclusion: Based on the findings of the present study more than 90% of ED residents had experienced at least one type of verbal, physical, or racial-ethnic violence during their shifts. It is necessary for residents in EDs to be trained about violence control and also report and follow these issues through legal channels.